Efektivitas, Kontribusi, dan Strategi Kebijakan Berbasis Fishbone pada Pajak atas Makanan dan/atau Minuman, Jasa Perhotelan, serta Jasa Kesenian dan Hiburan dalam Mendukung PAD Jakarta - Edietha Marshanda Putri; Hafifah Nasution; Putri Haryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study analyzed the effectiveness and contribution of the Food and/or Beverage Tax, Hotel Services Tax, and Art and Entertainment Services Tax to Jakarta's Regional Own-Source Revenue during 2018–2024, and formulated policy recommendations based on fishbone (Ishikawa) analysis for the lowest-performing tax type. A descriptive quantitative approach supported by qualitative analysis was employed. Secondary data were obtained from Regional Government Financial Reports, while primary data were gathered through in-depth interviews with the Regional Revenue Agency, a tax consultant, an event organizer, and a venue operator. The Hotel Services Tax recorded the highest average effectiveness at 108.25%, followed by the Food and/or Beverage Tax at 100.72%, and the Art and Entertainment Services Tax at 98.88%. All three fell under the very low contribution category, with the Art and Entertainment Services Tax recording the lowest average at 1.16%. Fishbone analysis identified six root cause categories: disproportionate staffing and insufficient socialization (Man), reactive collection mechanisms (Method), limited tax technology implementation (Machine), misclassified business data and weak regulatory dissemination (Material), underreported revenues and high tax rates suppressing voluntary compliance (Measurement), and high entertainment sector elasticity with slow post-pandemic recovery (Environment). Policy recommendations were formulated across all six factors to optimize regional tax revenue.